Metaphorical expressions and ethical appeals in Said Nursi's Damascus Sermon - Abdullah, Nur Sakinah Thomas; Hossein, Vahid Nimehchisalem; Mohd Kasim, Zalina; Mohamad Ali, Afida; Gulerce, Hakan (2015)
Contemporary cognitive linguistics views metaphor as pervasive in thoughts and conceptual in nature. Many ground-breaking facts on how human minds make use of metaphors have been revealed through research on cognitive sciences. Over the years, studies on conceptual metaphors in religious discourse have been conducted, but little is known about how orators make use of ethos (ethical appeals) and conceptual metaphors to influence their audience. This paper reports the results of a descriptive study which explores the influential Muslim thinker and theologian, Bediuzzaman Said Nursi’s (1877-1960) use of ethos and conceptual metaphors in his Damascus Sermon (1911). Specifically, this study identifies and interprets the metaphorical expressions used by Nursi which help him establish his ethos and strengthen his argument in the long run. The classical rhetoric theory is employed to examine the ethos while Lakoff and Johnson’s (1980) cognitive theory of metaphor is employed to analyse the conceptual metaphors in the Sermon. The analysis of the Sermon involves 3 main stages: i) the identification of selected extracts that indicate ethos, ii) the identification of linguistic metaphors and iii) the identification of the underlying conceptual mapping of the metaphorical expressions. In order to identify the linguistic metaphors, the Metaphor Identification Procedure (MIP) by PRAGGLEJAZ Group (2007) has been used. The findings show how the use of metaphors in the Sermon has contributed to the effectiveness of the ethical appeals made by Nursi, adding to his persuasive power. This study sets an antecedent for future studies on conceptual metaphors in religious discourse as a mechanism for rhetorical appeals.